II CONCURSO DE EMPRESAS SOCIAIS DA PUC MINAS BETIM - TEODÓSIO , ARMINDO DOS SANTOS DE SOUSA; PEREIRA, RAMON JUNG; SILVA MELO , JAQUELINE; DE MELO , TATIANE LÚCIA; DE OLIVEIRA , OSVALDO MAURÍCIO (Sinapse Múltipla, 2019)